Management of maxillary impacted canines: A prospective study of orthodontists' preferences - Hamad Alqahtani (Elsevier, 2021)
Background: Maxillary canines are considered the most commonly impacted teeth, after the third molars. Orthodontists have different preferences on how to approach maxillary impacted canines (MIC). The objective of this article was to investigate orthodontists' approach to managing MIC. Material and methods: A cross-sectional study comprising a comprehensive survey with 22 questions was sent to practicing orthodontists. This study explored the preferred diagnostic measures, surgical techniques, materials, and mechanics utilized to manage MIC;104 responses were returned. Results: Palatal impaction was reported to be encountered more often than labial impaction by 60% of the respondents. In 62% of the respondents, an oral and maxillofacial surgeon was the specialist preferred to perform the surgical exposure. In 66%, the choice of required surgical techniques was reported as a joint decision between orthodontists and other specialists who perform the surgery. Cone-beam computed tomography (CBCT) was reported to be the diagnostic x-ray of choice. The gold button with a chain was the preferred bonded attachment in 86% of cases. Less than half of the respondents bonded the attachments themselves during surgical exposure. A clear plastic retainer was the preferred retainer in 61% of the respondents, and 43% of the respondents tended to use a closed exposure technique. Coe-pakTM was the preferred surgical pack for orthodontists who prefer an open exposure technique. Piggyback (double wire) was the preferable mechanic to move a palatally impacted canine. Conclusion: Our findings indicate that there are variations among orthodontists on how to manage MICs in terms of diagnostic methods, surgical management, materials, and mechanics.